Musik sebagai Media Dakwah dalam Pandangan Syafi’iyah - Rahwan; Mukhammad Baharun (Maddah : Jurnal Komunikasi dan Konseling Islam, 2022)
Music is one of the habits of Indonesian people in conveying their dakwah about Islam. Pre- aching through music is very easy to accept among the general public, because the majority of dakwah recipients love the art of singing music, and music is not new among Shafi’iyah scho- lars. Differences of opinion about singing and music have yet to find results. Those who justify and forbid have a strong proposition. However, the prohibition of singing and music is not ab- solute. When singing and music are used for good things, the law is allowed. Preaching through singing and music is one way to use both for good things. Thus, preaching through the singing and music of the law is permissible. The ability to utilize music as a proselytizing medium must pay attention to several factors that barrier the ability to utilize singing and music. There are five factors that must be considered in using music as a medium of da’wah, namely: singer factor, to- ol factor, listener factor, song content, listener condition factor as a layman. Regarding musical instruments, Shafi’iyah scholars punished him by dividing it into two. First, musical instruments are allowed; Second, banned musical instruments. Musical instruments that agreed allowed by the jumhur ulama only duff (tambourine or musical instruments that were hit). Regarding other musical instruments, Shafi’iyah are still at odds in punishing them.